[Letter] Bishopsbourne, Nairobi [to Mr.] Hooper - Heywood, R. S. (Adam Matthew Digital, 1930)
Typescript letter from Bishop Heywood to H.D. Hooper about the response of CMS personnel to events in Kikuyu and the activities of the Kikuyu Central Association